THE ANALYSIS OF THE ANTIBIOTIC USE TOWARDS SURGICAL SITE INFECTION ON THE PATIENTS OF GASTROINTESTINAL SURGERY AT PKU MUHAMMADIYAH HOSPITAL YOGYAKARTA - Imaniar Noor Faridah; Tri Murti Andayani; Inayati Inayati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Surgical Site Infection / SSI is the result of the contamination of bacteria which enter the body as the surgery is in progress. High risk of Surgical Site Infection occurs in gastrointestinal surgery and is influenced by some characteristics, such as the use of antimicrobial prophylaxis. This research was aimed at identifying the use of antibiotics, identifying the percentage of the occurrence of Surgical Site Infection on the patients of gastrointestinal surgery. The research is a cross sectional research conducted prospectively at PKU Muhammadiyah Hospital Yogyakarta. The research subjects were all inpatients suffering gastrointestinal surgery and using antibiotic during the period of January until March 2012, and there are 68 patients fulfill the inclusion criteria. The inclusion criteria of the research is inpatient suffering gastrointestinal surgery, surgical site is visible, and use antibiotic for preventing Surgical Site Infection. Data that were analyzed comprised the use pattern of prophylactic antibiotics both perisurgery and post-surgery, and the analysis of the occurrence of Surgical Site Infection. The result of the research indicated that prophylactic antibiotics that was given to 14 patients with the most frequently used antibiotic was ceftriaxone (7.35%); perisurgical antibiotics that was given to 16 patients with the most frequently used antibiotics was the combination of ceftriaxone and metronidazole (8.82%), post-surgical antibiotics was given to all patients intravenously or orally in which the most frequently used intravenous antibiotics was ceftriaxone (30.88%) and the most frequently used oral was the quinolones (33.33%) and the most frequently used antibiotic type was cefadroxil (25%). The Surgical Site Infection occurred to 2 patients (2.94%) in contaminated surgery, with the comorbidity of non-diabetic, and they did not use prophylactic antibiotics.Key words: gastrointestinal surgery, occurrence of surgical site infection, prophylactic antibiotics